A velhice masculina: até quando caixeiros viajantes? - Bombana, Marilene (2005)
This paper discusses the aspects of ageing on gender perspective. Its focus is on the ageing male presented through a dialogue involving two characters: the first, fictional, extracted from the Arthur Miller's play Death of a Salesman , that experiences a bitter and painful ageing process; the second, real, described by a typical subject which exposes a narration of a sweet elderly, lived as opportunity of development, creativity and satisfaction. In the interlocution environment, it develops contents regarding to masculinity construction, with emphasis on work related questions, retirement and occupation in the post-work period. In this context, it points out the diversity of ageing process, as well as the importance of againstgeneralizator elder valorization